EAP alignment in EFL writing courses towards developing student’s academic writing skills - Melaku Bayu Workie; Zelealem Shitahun Haregu (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
The objective of the present study was to assess the prevailing alignment of English for academic purposes (EAP) in EFL writing courses vis-à-vis the development of academic writing skills of students in public universities of Amhara National Regional State (ANRS) in Ethiopia. The study used a descriptive survey that involved quantitative and qualitative methods. A questionnaire, focus-group discussions, and syllabus and materials survey were used to gather primary and secondary data, respectively, for the study. The descriptive statistics were employed in analyzing the quantitative data. The qualitative data were analyzed and reported thematically. The results showed there were existed a comparable horizontal (cross-department) distribution pattern of common writing courses among the three universities; all learners in taking the common course 'Basic Writing Skills' in each university learnt with the same syllabus and material regardless of their fields of study. So, there was a poor alignment of writing courses with the target students' mainstream discipline (i.e., learning and discourse) both in terms of content and genre.